STRATEGY FOR IMPLEMENTING TOLERANCE ATTITUDE BASED ON ISLAMIC EDUCATION - Abdul Razak Imamudin (Universitas Islam Malang, 2023)
This research aims to determine the cultivation of an attitude of tolerance in society and explain the strategies used by Islamic religious education teachers to instill an attitude of tolerance, as well as describe the results obtained by instilling an attitude of tolerance in society. To achieve the above objectives, a qualitative research approach was used which contains an explanation of the data obtained in the field. The key instrument is the researcher himself, and the data collection techniques used are observation and interviews. Data is analyzed by processing data from the source, presenting data and drawing conclusions. Research evaluation shows that the attitude of tolerance that is instilled is an attitude of tolerance and tolerance in the social life of society. The strategy used by preachers is a learning method that encourages understanding and practice as well as discussing what has been learned. Also, another strategy is to involve the community directly in group issues. The attitude of tolerance that is reflected in society is increasing cooperation and mutual cooperation regardless of the social status of the community and being able to resolve problems that arise in groups due to diversity.